Calypso [compact disc, unabridged] - Sedaris, David; Hart, Daniel, 1976- (Hachette Audio, 2018)
David Sedaris sets his formidable powers of observation toward middle age and mortality. This is beach reading for people who detest beaches, required reading for those who loathe small talk, and also Sedaris' darkest and warmest book yet.